1989
DOI: 10.1007/bf00274534
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with only one allele for a functional insulin receptor have a tendency to hyperinsulinaemia but not to hyperglycaemia

Abstract: Summary. Recently, we described a leprechaun patient with a genetically transmitted severe insulin resistance due to the absence of functional insulin receptors as inferred from the loss of insulin binding to the patients' fibroblasts and the impaired autophosphorylation of the [~-chain of the receptor. This patient was homozygous for the genetic defect which was recently found to be a leucine to proline mutation at position 233 in the a-chain of the insulin receptor. In the present study we have examined insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Family studies showed that heterozygous relatives have modest to marked insulin resistance without any definite clinical phenotype (Lekanne-Deprez et al, 1989). In-vitro study of the expressed mutant receptor shows that the mutation inhibits cleavage and transport of the pro-receptor to thecell-surface.…”
Section: General Consequences Of Severe Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Family studies showed that heterozygous relatives have modest to marked insulin resistance without any definite clinical phenotype (Lekanne-Deprez et al, 1989). In-vitro study of the expressed mutant receptor shows that the mutation inhibits cleavage and transport of the pro-receptor to thecell-surface.…”
Section: General Consequences Of Severe Insulin Resistancementioning
confidence: 99%
“…Leprechaun Geldermalsen is the offspring of a consanguineous marriage and is homozygous for a Leu-+Pro mutation at codon 233 in the a-subunit (Klinkhamer et al, 1990). Family studies showed that heterozygous relatives have modest to marked insulin resistance without any definite clinical phenotype (Lekanne-Deprez et al, 1989). In-vitro study of the expressed mutant receptor shows that the mutation inhibits cleavage and transport of the pro-receptor to thecell-surface.…”
Section: Leprechaunismmentioning
confidence: 99%
“…In certain cases heterozygous relatives of such patients have had no obvious clinical features except moderate to marked h}~erinsulinaemia and sometimes, impairment of glucose tolerance [2]. This has led to increased interest in the possibility that a certain proportion of subjects with "typical" Type 2 (non-insulin-dependent) diabetes mellitus may harbour such mutations and that these might contribute to the inherited insulin resistance component of the disease.…”
mentioning
confidence: 98%
“…The underlying molecular mechanism is not clear, although recent findings suggest the involvement of the insulin receptor (Kadowaki et al, 1988;Yoshimasa et al, 1988 (Lekanne Deprez et al, 1989). Cloning and sequencing of the patient's insulin receptor cDNA revealed a leucine-to-proline mutation at position 233 in the ca subunit.…”
mentioning
confidence: 98%